Perbandingan Nilai Pengetahuan Sebelum dan Sesudah Penyuluhan Ispa di Puskesmas Cikupa Tahun 2022 - Theresia Fitriyana Dwi Kristianti; Citra Setyorini; Giovanno Sebastian Yogie; Clement Drew (Pusat Riset dan Inovasi Nasional, 2023)
Upper respiratory tract infection (URTI) is an irritation and swelling of the upper respiratory tract associated with cough and no proof of lower respiratory tract disease. According to RISKESDAS in 2018, the prevalence of URTI in Indonesia is 4,4%. Banten is eighth highest province with URTI in Indonesia. Tangerang is second highest regency with URTI in Banten. Poor knowledge of URTI is a risk factor of URTI. Method: The study is an analytic study with quasi experimental design in which health education were performed and respondent knowledge are compared before and after and further analyzed with paired t-test analysis. Result: of the 31 respondence, 27 (87,1%) is female, 15 (48,4%) is senior high school graduate, and 15 (48,4%) is housewife. The average score of pre-test is 62,16 and the average score of post-test is 90,69. There is a significant difference between pretest and post-test score (p <0,001). Conclusion: There is a significant difference between before and after health education.